The influence of generation Y students' perceptions of brand communication, service quality and brand satisfaction on brand loyalty in technical and vocational education training colleges in Gauteng - Ramuthivheli, Itani Listen (Vaal University of Technology, 2022)
Due to the rapidly evolving and dynamic nature of the South African higher education sector, it is critical that institutions communicate their brands to stakeholders to enhance their perception of the institution as a quality service provider. Despite this, little attention has been paid to the influence of brand communication, brand satisfaction and service quality on brand loyalty in higher education, particularly in technical and vocational education and training (TVET). Research has demonstrated a positive relationship between brand communication, service quality, brand satisfaction and brand loyalty in the service sector; however, it is unknown whether such a relationship exists in the South African TVET sector. It is essential to investigate how Generation Y students perceive brand communication, brand satisfaction and service quality in the TVET sector in Gauteng. Five TVET colleges were used as a convenience sample to recruit 500 students. In each college, students were given a self-administered questionnaire to complete during class time. The data was analysed using various statistical methods, including exploratory factor analysis, descriptive statistical analysis, correlation analysis and structural equation modelling. The results of the study show that service quality and brand satisfaction have a strong positive influence on brand loyalty. However, the structural model results indicate that this study does not support a relationship between brand communication and brand loyalty. However, there was a significant influence of service quality on brand loyalty towards TVET colleges. In other words, students who have had positive experiences in contact with vocational colleges and are generally satisfied with the services they provide, will undoubtedly develop loyal inclinations towards them. The study also shows that brand loyalty is positively related to brand satisfaction. This study contributes to the body of knowledge by empirically testing a model of the factors influencing brand loyalty among Generation Y students in TVET colleges. The study shows that brand communication, service quality and customer satisfaction are important factors that influence brand loyalty.
M. Tech. (Department of Marketing Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Students’ perceptions; Brand communication; Service quality; Brand satisfaction; Brand loyalty; Technical and vocational training.; Dissertations, Academic -- South Africa.; Brand loyalty.; Branding (Marketing).; Communication in organizations.